The Link Between Hate Speech and Terrorism: A Critical Analysis of Indonesia’s Legal Framework - Alhakim, Abdurrakhman; Situmeang, Ampuan; Tan, David; Febriyani, Emiliya (Universitas Islam Negeri Raden Fatah Palembang, 2024)
Hate speech and terrorism are two forms of crime that are similar in their discriminatory nature. The efforts to address these crimes are of significant importance, as they starkly contrast with the values that Indonesia holds dear and present serious threats to its multicultural society. This study aims to explore the correlation between hate speech and terrorism and to explain how this correlation may assist in the development of a legal framework that better addresses both issues. The research employed a normative legal approach to analyze the existing positive laws regarding hate speech and terrorism, aiming to identify correlations between the two. This normative legal research utilized a combined statutory approach, employing primary law sources as secondary data. The analysis revealed normative issues within the Indonesian legal framework that restrict the criminalization of offenses that fall between the legal definitions of hate speech and terrorism. These issues need to be addressed as an important step in Indonesia’s legal development to realize a safe society for all Indonesians.